2020
DOI: 10.1016/j.cmpb.2019.105244
|View full text |Cite
|
Sign up to set email alerts
|

Fast computation of soft tissue thermal response under deformation based on fast explicit dynamics finite element algorithm for surgical simulation

Abstract: Background and Objectives: During thermal heating surgical procedures such as electrosurgery, thermal ablative treatment and hyperthermia, soft tissue deformation due to surgical tool-tissue interaction and patient movement can affect the distribution of thermal energy induced. Soft tissue temperature must be obtained from the deformed tissue for precise delivery of thermal energy. However, the classical Pennes bio-heat transfer model can handle only the static non-moving state of tissue. In addition, in order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Polousky et al [96] reported electrosurgery as an effective tool for arthroscopic meniscectomy. Zhang and Chauhan [90] proposed a thermal analysis under tool-tissue defor-mation based on the fast explicit dynamics finite-element algorithm (FED-FEM). The FED-FEM uses an explicit time integration scheme and computes the nodal load, in this case thermal load, at the element level.…”
Section: ) Mesh-based Modeling Methodsmentioning
confidence: 99%
“…Polousky et al [96] reported electrosurgery as an effective tool for arthroscopic meniscectomy. Zhang and Chauhan [90] proposed a thermal analysis under tool-tissue defor-mation based on the fast explicit dynamics finite-element algorithm (FED-FEM). The FED-FEM uses an explicit time integration scheme and computes the nodal load, in this case thermal load, at the element level.…”
Section: ) Mesh-based Modeling Methodsmentioning
confidence: 99%
“…In order to verify the accuracy of the model proposed in this paper, the standard modeling software ANSYS was used to establish a reference model [16], we compared the standard mean square deviations of the nodal displacements of the three models relative to the reference model under the same force conditions. These three models are the model proposed in this paper, the co-rotating finite element model [17], and the finite element model based on neural network [18].…”
Section: Accuracymentioning
confidence: 99%
“…We employ a transformation of system configurations to achieve bioheat computation on deformed soft tissues [53]. The mapping function for deformations 𝛺 0 → 𝛺 𝑡 can be defined by…”
Section: Mathematical Modelling Of Bioheat Transfer Under Soft Tissue...mentioning
confidence: 99%
“…To achieve fast and accurate numerical solutions, we develop solution procedures based on the (i) fast explicit dynamics finite element algorithm [55] for transient bioheat computation [56] under soft tissue deformations [53] and the (ii) total Lagrangian explicit dynamics finite element algorithm [57] for biomechanics computation of large-strain soft tissue deformations. The proposed formulation has not been evidenced in previous works.…”
Section: Thermo-visco-hyperelastic Total Lagrangian Explicit Dynamics...mentioning
confidence: 99%